Dinamika Sejarah Perkembangan Ekonomi dan Kebijakan Pembangunan di Era Reformasi dan Neoliberalisme - Pramudita, Dafina; Hany Nurpratiwi; Haikal Jiddan Yusuf; Putri Mei Seninandita (Historia Pedagogia, 2025)
This study examines the transformation of Indonesia’s economic policies during the Reform Era and the influence of neoliberal doctrines on national development following the collapse of the New Order in 1998. Using a library research method, this study analyzes academic literature, institutional reports, and policy documents to identify patterns of policy change, forms of neoliberal penetration in strategic sectors, and their socio-economic consequences. The findings indicate that macroeconomic stabilization, banking restructuring, trade liberalization, privatization of state-owned enterprises, and fiscal decentralization successfully restored economic stability and increased foreign investment. However, these reforms also resulted in rising income inequality, uneven regional development, and commercialization of public services. The study concludes that the Reform Era generated macroeconomic recovery while simultaneously reinforcing socio-economic disparities, requiring corrective state policies to achieve inclusive development.